MicroRNAs miR-142-5p, miR-150-5p, miR-320a-3p, and miR-4433b-5p in Serum and Tissue: Potential Biomarkers in Sporadic Breast Cancer - Carvalho, Tamyres Mingorance; Brasil, Guillermo Ortiz; Jucoski, Tayana Schultz; Adamoski, Douglas; Lima, Rubens Silveira de; Spautz, Cleverton C.; Anselmi, Karina Furlan; Ozawa, Patricia Midori Murobushi; Cavalli, Iglenir João; Carvalho de Oliveira, Jaqueline; Gradia, Daniela Fiori; Ribeiro, Enilze Maria de Souza Fonseca (Frontiers in Genetics, 2022)
Breast cancer (BC) is a heterogeneous disease, and establishing biomarkers is essential to patient management. We previously described extracellular vesicle-derived miRNAs (EVs-miRNAs) miR-142-5p, miR-150-5p, miR-320a, and miR-4433b-5p in serum discriminated BC from control samples, alone and combined as a panel. Using these previously described markers, we intend to evaluate if the same markers identified in EVs are also potential biomarkers in tissue and serum. Expression analysis using RT-qPCR was performed using serum of 67 breast cancer patients (BC-S), 19 serum controls (CT), 83 fresh tumor tissues (BC-T), and 29 adjacent non-tumor tissue samples (NT). Additionally, analysis from The Cancer Genome Atlas (TCGA) data (832 BC-T and 136 NT) was performed. In all comparisons, we found concordant high expression levels of miR-320a and miR-4433b-5p in BC-S compared to CT in both EVs and cell-free (cf-miRNAs). Although miR-150-5p and miR-142-5p were not found differentially expressed in serum, panels including these miRNAs improved sensitivity and specificity, supporting our previous findings in EVs. Fresh tissue and data from the TCGA database had, in most comparisons, an opposite behavior when compared to serum and EVs: lower levels of all miRNAs in BC-T compared to NT samples. TCGA analyses revealed reduced expression levels of miR-150-5p and miR-320a-3p in BC-T compared to NT samples and overexpression of miR-142-5p in BC-T, unlike our RT-qPCR results from tissue in the Brazilian cohort. The fresh tissue analysis showed that all miRNAs individually could discriminate between BC-T and NT in the Brazilian cohort with high sensitivity and sensibility. Furthermore, combining panels showed higher AUC values and improved sensitivity and specificity. Additionally, lower levels of miR-320a-3p in serum were associated with poor overall survival in BC Brazilian patients. In summary, we observed that miR-320a and miR-4433b-5p distinguished BC from controls with high specificity and sensibility, regardless of the sample source. Additionally, lower levels of miR-150-5p and higher levels of miR-142-5p were statistically significant biomarkers in tissue, according to TCGA. When combined in panels, all combinations could distinguish BC patients from controls. These results highlight a potential application of these miRNAs as BC biomarkers.